Implementation strategy and marketing plan clinic slimmingfique slimming center - Calvien Pradiptha Giovannie; Rhian Indradewa; Rina Anindita; Tantri Yanuar Rahmat Syah (Enrichment : Journal of Management, 2023)
Awareness of healthy living is starting to become a lifestyle that can be said to be popular in Indonesia. According to a survey conducted by insurance agents in Indonesia, it was revealed that 73% of Indonesians put health as the most important thing. The existence of high awareness about exercising and consuming healthy food, as well as support from the environment and society, have an impact on creating better health. Today's business competition is getting tougher, and technological advances make it easier to get information and move forward in business. Information technology makes it easier for people to find what they are looking for (Heskiano, 2020). In the health sector, especially for obese people or those who want to maintain an ideal condition, they can easily get this information, which is very helpful for Slimmingfique, where Slimmingfique is the center for Slimming. is a start-up clinic because of the difficulty of overcoming the problem of obesity. Most people who undergo slimming programs fail because there is no support system to help them. Slimmingfique is a slimming center that invites individuals to live a healthy lifestyle that results in an ideal body weight. With the mentoring method, it is hoped that a healthy lifestyle will be maintained and the main mindset will change, so that after the program ends, customers can live a healthy lifestyle without coercion because they are used to it. Ideal body weight is achieved, which protects customers from other complications.